Detection of colistin susceptibility in extended spectrum β lactamases positive Klebsiella pneumoniae and Escherichia coli clinical isolates by broth disc elution method - Sivadas, Aiswarya; Sajeev, Anakha; Kumar K. S., Harish; Krishnan, Shinu (International Journal of Research in Medical Sciences, 2024)
Background: Antibiotic resistance is one of the greatest threats in human health. Extended spectrum β lactamases mediated resistance is prevalent worldwide, Klebsiella pneumoniae and Escherichia coli leap out as this significant ESBL producers conferring resistance to the expanded spectrum cephalosporins. Colistin is being administered as last line therapy for patients that have failed to respond to other available antibiotics that are active against Gram-negative bacteria. Methods: The present study was conducted at school of medical education Kottayam, Kerala from January 2023 to November 2023.During the period of study 150 isolates of K. pneumoniae and 136 isolates of E. coli were collected from various diagnostic microbiology laboratories in Kerala. The colistin susceptibility pattern of ESBL producing isolates was detected by broth disc elution method recommended by CLSI. Results: In this study prevalence of multi-drug resistant is 6% and 9.6% and Extensively-drug resistant is 62% and 63.9% for K. pneumoniae and E. coli respectively. ESBL production was detected as 72% in K. pneumoniae and 79% in E. coli. The colistin susceptibility pattern of ESBL producing K. pneumoniae and E. coli was detected as 76.9% and 87.9% respectively Conclusions: Our result demonstrated that the recent use of colistin as last resort treatment for extensively drug resistant gram-negative bacilli, it is essential to know the prevalence of susceptibility pattern to this antibiotic.